The influence of material microstructural characteristics on the strength of porous or composite ceramic coatings. (1st February 2022) - Zinoviev, A.; Balokhonov, R.; Zinovieva, O.; Romanova, V.
Abstract: This paper is a follow-up study to our earlier research that identified several types of preferred stress concentration regions in a material with a porous coating and suggested certain microstructural factors to induce them (Zinoviev et al., 2020 ). This study takes a closer look at each of the factors indicated earlier, examining their effects on the deformation and fracture of a coating and a coated material as a whole. Porosity, including a pore distribution, size, number, and distance between them, elastic property difference in a composite coating, curvilinear coating-substrate interface, and thickness of the pore-free coating layer are among the causative factors analyzed in microstructure-based mechanical simulations. It is found that the pore distribution controls the crack-initiation strain and first crack location while having a low effect on the elastic modulus. A dimensionless parameter is proposed to characterize the effect of the pore size and minimum distance between them on the local stress–strain state of a coating. The research findings provide insights for the choice of filler materials to be induced in a polymer-derived ceramic coating, suggesting the material resulting in the highest strength properties of the coated material among the considered ones. Analysis of the non-porous layer effect suggests that cracks form either at the coating-substrate interface or pore surface, and defined the layer thickness when the location of crack initiation changes. The insights gained from this study may be of assistance for coating design and engineering.